Effect of the COVID-19 pandemic on colorectal cancer screening in two university-affiliated health care systems - Vinod Kumar; Lilian Golzarri-Arroyo; Sarah Roth; Thomas F. Imperiale (PLoS ONE, 2025)
Objectives In two large university affiliated healthcare systems, we examined trends in colorectal cancer (CRC) screening both prior to and during the COVID-19 pandemic to compare the trends in non-invasive screening tests and colonoscopy. Materials and methods In this retrospective time-trend analysis, we obtained the numbers of colonoscopies and non-invasive tests performed monthly during the pandemic and the year prior to it. We obtained colonoscopy data from five endoscopy units with the indication determined by dual independent review. Monthly numbers of completed fecal immunochemical (FIT) and FIT-DNA tests were obtained from the electronic medical records of both health systems. Trends in testing, numbers, and stage of incident CRCs diagnosed during the 30-month interval were examined using Poisson regression and logistic regression, respectively. Results From January 2019 to June 2021, we identified 16,939 FIT tests, 2,942 FIT-DNA tests, and 38,332 colonoscopies from the two health systems, and 368 colorectal cancers (105 early stage, 263 advanced stage) from the private hospital system. Overall colonoscopy volume declined by 18.7% (from 16,483 to 13,393) in 2020 compared to 2019 in both health systems, returning to baseline in 2021. Non-invasive tests declined by 21.9% in 2020, but increased in 2021 due to greater use of FIT/DNA. Compared to 2019, incident CRCs declined in 2020 but rebounded in 2021, with no difference in early versus late-stage cancers. Conclusions These trends in CRC screening tests may be useful for modeling the effects of the pandemic on the longer-term outcomes of CRC incidence and mortality.